Cutting-edge carbon-based architectures for energy production and conversion - Adeola, Adedapo O.; Adedipe, Demilade T.; Adenuga, Dorcas O.; Kyesmen, Pannan I.; Olaremu, Abimbola G.; Ijagbuji, Ayodeji A.; Oloye, Femi F. (Frontiers in Carbon, 2025)
Carbon-based materials are pivotal in next generation energy technologies due to their tunable electronic properties, porosity, and chemical stability. Structural variations from 0D to 3D; graphene, carbon nanotubes, carbon aerogels, and biomass derived activated carbons; enable multifunctional roles as conductive scaffolds, catalysts, adsorbents, and enzyme supports. In biofuel production, they enhance biomass pretreatment, fermentation, and biodiesel synthesis, achieving up to 95% biodiesel yields and 30%–50% faster fermentation. In thermochemical processes, porous carbons improve hydrocarbon cracking, deoxygenation, and tar conversion, boosting selectivity by 20%–40% and reducing byproducts by 25%. For CO2 valorization, carbon nanomaterials enable selective conversion with Faradaic efficiencies >80% and CO2-to-methanol rates up to 0.5 mmol g-1 h-1. In solar and hydrogen technologies, they enhance charge transport, stability, and catalysis, delivering photocurrents of 15–25 mA cm-2, solar-to-hydrogen efficiencies of 12%–18%, and 40% higher H2 yields in biomass gasification. Heteroatom doping and surface functionalization allow precise control over activity and selectivity. Despite scalability and integration challenges, AI-guided design, waste derived carbons, and hybrid architectures promise sustainable, high performance solutions. This review underscores carbon’s role in bridging fundamental science and industrial applications, driving the transition toward a sustainable energy future.